2020
DOI: 10.5194/amt-2020-474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of particulate organic nitrates from thermodenuder-aerosol mass spectrometer measurements in North China Plain

Abstract: Abstract. Particulate organic nitrates (pON) are an important component of secondary organic aerosol in biogenic emission dominant environments, and play a critical role in NOx cycles. However, estimation of pON has been a challenge in polluted environments, e.g., North China Plain with high concentrations of inorganic nitrate and NOx. Here we developed a method for estimation of pON from the measurements of high-resolution aerosol mass spectrometer coupled with a thermodenuder based on the volatility differen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Particle-phase organic nitrates (pRONO 2 ) have recently emerged as a significant component of SOA in areas dominated by biogenic emissions, including in the Southeast United States, in the Rocky Mountains, across Europe, in the boreal forest, in the California Central Valley, , and in rural areas of both northern and southern China. A number of studies have also found significant contributions of pRONO 2 to SOA in regions of oil and gas production, including in the Alberta Oil Sands and in the Uintah Basin . Recent observations have shown that organic nitrates are a significant contributor to OA in Chinese cities. , Specifically, Yu et al found that organic nitrates make up 9–25% of OA during spring-autumn in urban Shenzhen, and the dominant precursors to pRONO 2 included both biogenic (α-pinene, limonene, and camphene) and anthropogenic (styrene) VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…Particle-phase organic nitrates (pRONO 2 ) have recently emerged as a significant component of SOA in areas dominated by biogenic emissions, including in the Southeast United States, in the Rocky Mountains, across Europe, in the boreal forest, in the California Central Valley, , and in rural areas of both northern and southern China. A number of studies have also found significant contributions of pRONO 2 to SOA in regions of oil and gas production, including in the Alberta Oil Sands and in the Uintah Basin . Recent observations have shown that organic nitrates are a significant contributor to OA in Chinese cities. , Specifically, Yu et al found that organic nitrates make up 9–25% of OA during spring-autumn in urban Shenzhen, and the dominant precursors to pRONO 2 included both biogenic (α-pinene, limonene, and camphene) and anthropogenic (styrene) VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…For the existing OA which is sampled into the OFR, the evaporation of input OA upon heating can be roughly estimated based on the results of thermal denuder (TD) experiments, in which the aerosols were heated from ambient/room temperatures (20-25 °C ) to higher temperatures (typically 60-200 °C ) at a typical residence time of 10-60 s (typically ~20 480 s) (Huffman et al, 2009;Xu et al, 2020;Hu et al, 2016;Saha et al, 2017;Kolesar et al, 2015;Saha and Grieshop, 2016;Lee et al, 2011). Previous studies suggest the evaporation of aerosol is kinetically limited, which varies with temperature, residence time, OA mass and volatility, phase state and dissociation rates for oligomers (Cappa, 2010;Riipinen et al, 2010;Roldin et al, 2014;Schobesberger et al, 2018).…”
Section: Temperature Influence On Soa Formationmentioning
confidence: 99%